Edukasi Berbasis Konsep 3R untuk Meningkatkan Pengetahuan Pengurangan Food Waste pada Ibu Rumah Tangga - Husna Dwimulya; Zahra Nurfadilah; Restu Ediyani Utami; Putri Novitasari (LPPPM STAI Darul Hikmah Bangkalan, 2026)
Food waste is a significant environmental, economic, and social issue. In Pakutandang Village, Bandung Regency, many households purchase food without proper planning, leading to daily food waste. This community service aimed to increase the knowledge of households, especially housewives, about waste management using the 3R (reduce, reuse, recycle) concept with a behavioral change-oriented education approach. The educational program was conducted using a one-group pretest-posttest approach with 53 participants comprising housewives with toddlers. Instrument validity was verified prior to application, and data were analyzed using the Paired t-test. Results showed a statistically significant improvement in knowledge after the education session (p<0.05), with posttest scores increasing by 5% compared to the pretest. This program highlights the importance of behavioral education in reducing food waste, and future initiatives require continuous evaluation and structured training in compost production. Keywords: food waste, waste management, 3R concept, community education, household behavior